2009
DOI: 10.1103/physrevb.79.125202
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic picture of Co clustering in ZnO

Abstract: Density functional theory was applied to study the chemical and magnetic interactions between Co atoms doped in ZnO. It was found that the Co impurities tend to form nanoclusters and the interactions between these atoms are antiferromagnetic within the local spin-density approximation ͑LSDA͒ + Hubbard U approach. The extracted interatomic exchange parameters agree reasonably well with recent experimental results. We have analyzed and compared the electronic structure obtained using the LSDA and LSDA+ U approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
24
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 34 publications
4
24
1
Order By: Relevance
“…Also, we have taken into account the effect of the magnetic exchange energy, exploring ferro-and antiferro-magnetic orderings in all structures modelled. Its value depends on the specific surface under study, but generally lies between 0.03 eV/Co (for neighbouring isolated impurities) and 0.08 eV/Co (for 2D aggregates), in good agreement with previous estimates when available, 6 formation of Co clusters. All results presented here correspond to the ground state magnetic configuration.…”
supporting
confidence: 76%
See 1 more Smart Citation
“…Also, we have taken into account the effect of the magnetic exchange energy, exploring ferro-and antiferro-magnetic orderings in all structures modelled. Its value depends on the specific surface under study, but generally lies between 0.03 eV/Co (for neighbouring isolated impurities) and 0.08 eV/Co (for 2D aggregates), in good agreement with previous estimates when available, 6 formation of Co clusters. All results presented here correspond to the ground state magnetic configuration.…”
supporting
confidence: 76%
“…5 Moreover, a clear tendency of substitutional Co to aggregate in bulk ZnO has been found. 6,7 However, little is known about the influence of surfaces or boundaries in the distribution of Co impurities. This is in spite FM in DMO seems to be largely favoured in low dimensional structures and close to interfaces.…”
mentioning
confidence: 99%
“…The tendency of Co clustering in dilute magnetic oxides has already been observed in TiO 2 :Co, 4 in this study it was found that the Co atoms prefer to be in a "close" geometry, and thus form metallic clusters. 29,30 In contrast to this, Co in ZnO shows no sign of surface clustering and very closely resembles the Co 2+ spectrum of Co(OH) 2 .…”
Section: Ironmentioning
confidence: 82%
“…9,10 Furthermore, this tendency was also suggested by a detailed density functional study of the chemical and magnetic interactions between substitutional Co ions in ZnO. 11 Therefore, a universal substitutional clustering via oxygen seems to apply to all these DMO. Since Co dimers in ZnO are known to couple antiferromagnetically via O-mediated superexchange in contrast to paramagnetic isolated Co monomers, the substitutional Co clustering in ZnO can dominate its magnetic properties.…”
mentioning
confidence: 85%
“…This finding is in agreement with the theoretical calculation results of Co-doped ZnO with a smaller Co doping level of 5.6% using local spin-density approximation. 11 Furthermore, the tendency towards substitutional clustering was evidenced experimentally by x-ray absorption fine structure (XAFS) in Co-doped ZnO with low Co concentrations of 0.5% and 2%.…”
mentioning
confidence: 98%